2013
DOI: 10.1002/bip.22288
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism and electron microscopy studies in vitro of 33‐mer gliadin peptide revealed secondary structure transition and supramolecular organization

Abstract: Gliadin, a protein present in wheat, rye, and barley, undergoes incomplete enzymatic degradation during digestion, producing an immunogenic 33-mer peptide, LQLQPF(PQPQLPY)3 PQPQPF. The special features of 33-mer that provoke a break in its tolerance leading to gliadin sensitivity and celiac disease remains elusive. Herein, it is reported that 33-mer gliadin peptide was not only able to fold into polyproline II secondary structure but also depending on concentration resulted in conformational transition and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 70 publications
5
58
0
Order By: Relevance
“…Peptides may enter the cell by endocytosis, with their entrance into the cells requiring 37 °C temperature and Ca 2+ in the media [84]. It has been shown that these peptides possess structural configuration characterized by a left-handed polyproline II helical conformation that is preferred by MHC class II ligands [85]. …”
Section: Gluten Intolerance Pathogenesismentioning
confidence: 99%
“…Peptides may enter the cell by endocytosis, with their entrance into the cells requiring 37 °C temperature and Ca 2+ in the media [84]. It has been shown that these peptides possess structural configuration characterized by a left-handed polyproline II helical conformation that is preferred by MHC class II ligands [85]. …”
Section: Gluten Intolerance Pathogenesismentioning
confidence: 99%
“…Electron microscopy observations show that the 33‐mer can oligomerize to form nanospheres, fibrils, and fibers that coexist together at 613 μ m . Molecular dynamics simulation and partial charge distribution calculations have revealed that the 33‐mer peptide is a nonionic amphiphile with the capability to form, at least, a stable dimer …”
Section: The Supramolecular Behavior Of 33‐mer Gliadin Peptide: a Newmentioning
confidence: 99%
“… Spontaneous oligomerization of 33‐mer depends on peptide concentration. On increasing the peptide concentration, spherical‐like oligomers undergo a conformational transition towards sheet‐like structures with a parallel β structure …”
Section: The Supramolecular Behavior Of 33‐mer Gliadin Peptide: a Newmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, time-dependent CD experiments confirmed the slow transition from unordered to ordered oligomers in the first 3h (Figure 3C), as evidentb yt he slow increaseo ft he minimaa tl % 215 nm and the maxima at l = 195 nm until 7h.A ni sodichroic point was observed at l = 208 nm, which suggesteda two-state transitionf rom randomc oil to b-sheet conformation ( Figure 3C). [36] CD deconvolution with the algorithm BeSt-Sel [37,38] revealed an increase in the amount of b sheets within 1h ( Figures 3D and S3). The ratio between b-sheet structure and unordered conformation increased by 84 %f or 5h.T he antiparallel b-sheet structure, formed in the early oligomerization phase, is the major component that tends to increase during the first hour.S uccessively,t he decrease in the antiparallel component is compensated for by an increasei nt he parallel one ( Figure 3D).…”
mentioning
confidence: 99%